Microvascular disease in diabetes - 4 0 16; 1976- Tecilazich, Francesco; 5 (Hoboken, NJ : Wiley-Blackwell, 2020)
Diabetes remains one of the main causes, in the western world, of legal blindness, end stage renal disease, and amputation, despite the implementation of tight glycemic control and the great progress in the management and care of our patients. In the perspective that clinical and basic-science knowledge are fundamental to clinicians as well as to researchers, this book is a valuable resource by integrating clinical information and research frontlines of the microvascular complications of diabetes. It will provide up-to-date diagnostic criteria, classifications, and therapeutic approaches and recent discoveries on mechanisms of disease, experimental therapeutic agents, and biomarkers of disease. The ultimate goal of this book is to provide a useful and handy tool to professionals and students in the field of diabetes and its microvascular complications. Will provide a much-needed resource synthesizing research and clinical applications to treating microvascular complications of diabetes. Covers all relevant microvascular systems. Provides current diagnostic criteria, classifications, and therapeutic approaches, as well as recent discoveries on the mechanisms of disease, experimental therapeutic agents, and biomarkers of disease--
Pathophysiology / Francesco Tecilazich -- Genetics of diabetic microvascular disease / Niina Sandholm, Carol Forsblom -- Epigenetics of Diabetic Microvascular Disease / Luciano Pirola -- Diabetic Retinopathy - Clinical / Francesco Bandello, Rosangela Lattanzio, Alessandro Marchese, Emanuela Aragona -- Diabetic retinopathy - Research / Gopalan Gnanaguru -- Diabetic Nephropathy - Clinical / Gianpaolo Zerbini -- Diabetic Nephropathy - Research / Silvia Maestroni, Gianpaolo Zerbini -- Diabetic Neuropathy - Clinical / Christopher H. Gibbons, -- Diabetic Neuropathy - Research / Krish Chandrasekaran, Lindsay A. Zilliox, James W. Russell -- Diabetic Foot, Clinical / Cristian Nicoletti -- Diabetic Foot - Research / Theocharidis Georgios, Aristidis Veves -- Coronary Microvascular Dysfunction Clinical and Research / Guglielmo Gallone, Francesco Moroni, Marco Magnoni -- Cerebral Microvascular Disease Clinical and Research / Eelco van Duinkerken, Richard G. IJzerman
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; Diabetic Angiopathies;Diabetes Mellitus -- 20; 20; 2